Operation of a dual-phase xenon detector with wavelength sensitivity from ultraviolet to infrared - Hammann, Robert; Böse, Kai; Form, Steffen; Hötzsch, Luisa; Marrodán Undagoitia, Teresa (Frontiers in Detector Science and Technology, 2025)
Xenon, in both its gaseous and liquid phase, offers excellent scintillation and ionization properties, making it an ideal target medium for rare event searches. We report on measurements performed with a dual-phase xenon time projection chamber sensitive to wavelengths from 170 nm to 1700 nm. In addition to the well-established ultraviolet (UV) scintillation, we observe coincident signals in a photomultiplier tube sensitive to infrared (IR) light, associated with both prompt scintillation in the liquid and electroluminescence in the gas. We study the time response of the IR signals and their dependence on the applied amplification field in the gas. Our findings support the observation of IR emission from electroluminescence and reveal a time response distinct from that previously reported for α-particles in gas. The results suggest that IR scintillation could provide enhanced signal identification and background rejection in future xenon-based detectors.